2006
DOI: 10.1063/1.2337255
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of MnGa2Se4 in the temperature range of 2–300K

Abstract: Measurements of low field static magnetic susceptibility and of magnetization with pulsed magnetic fields up to 32T have been made as a function of temperature on polycrystalline samples of the compound MnGa2Se4 which has a tetragonal structure. The resulting data have been used to give information on the magnetic spin-flop and magnetic saturation transitions. It has been found that MnGa2Se4 has a zero-field Néel temperature TN of 8.1K and shows a triple point at (7.8K, 2.2T). Details of the magnetic B-T phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This magnetic behavior was associated with the Mn configuration on the respective crystal structure. More recently, 6 the magnetic phase diagram was determined and it was found that MnGa 2 Se 4 has a zero-field Néel temperature T N of 8.1 K, showing a triple point at 7.8 K and 2.2 T. In an earlier work, 7 the optical energy gap E g of MnGa 2 Se 4 has been measured as a function of pressure up to 13 GPa, and it was shown that the tetragonal ordered phase is a direct gap semiconductor ͑E g = 2.7 eV at 300 K͒. It was found that the direct energy gap increases linearly with the applied pressure at the rate of 2.5ϫ 10 −2 eV/ GPa up to 4.1 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…This magnetic behavior was associated with the Mn configuration on the respective crystal structure. More recently, 6 the magnetic phase diagram was determined and it was found that MnGa 2 Se 4 has a zero-field Néel temperature T N of 8.1 K, showing a triple point at 7.8 K and 2.2 T. In an earlier work, 7 the optical energy gap E g of MnGa 2 Se 4 has been measured as a function of pressure up to 13 GPa, and it was shown that the tetragonal ordered phase is a direct gap semiconductor ͑E g = 2.7 eV at 300 K͒. It was found that the direct energy gap increases linearly with the applied pressure at the rate of 2.5ϫ 10 −2 eV/ GPa up to 4.1 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows a typical variation of 1 / with T for 2 K Ͻ T Ͻ 300 K obtained for the sample with z = 0.85, zero-field cooled ͑ZFC͒ ͑heating curve͒ and field cooled ͑fc͒ ͑cooling curve͒ data being shown. 5 This is attributed to the presence of a slight residual amount of disorder in the specimen, despite the very long anneal during preparation. 2͑a͒, it is seen that the peak at T N is slightly broadened and not as sharp as for an ideal semiconductor, this form was also observed for the MnGa 2 Se 4 sample.…”
Section: A Magnetic Susceptibility Measurementsmentioning
confidence: 99%
“…In the last few years, the emphasis in the study of these compounds has been on their structural [1], magnetic [2], and optical proper ties [3][4][5][6]. Figure 1 presents the current-voltage (I-V) char acteristics of the MnGa 2 Se 4 single crystals.…”
mentioning
confidence: 99%